Recent developments and future prospects of all-metal aromatic compounds. (21st September 2015) - Mercero, Jose M.; Boldyrev, Alexander I.; Merino, Gabriel; Ugalde, Jesus M.
<x xml:space="preserve">Abstract</x> This review illustrates recent advances in extending aromaticity/antiaromaticity concepts to inorganic and all-metal rings in order to account for their electronic structure and stability.